Asymmetric Synthesis of 4, 4‐(Difluoro)glutamic Acid via Chiral Ni(II)‐Complexes of Dehydroalanine Schiff Bases. Effect of the Chiral Ligands Structure on the Stereochemical Outcome. Issue 1 (29th January 2020) - Tokairin, Yoshinori; Shigeno, Yuhei; Han, Jianlin; Röschenthaler, Gerd‐Volker; Konno, Hiroyuki; Moriwaki, Hiroki; Soloshonok, Vadim A.
Abstract: Four differently substituted chiral Ni(II)‐complexes of dehydroalanine Schiff base were prepared and reacted with BrCF2 COOEt/Cu under the standard reaction conditions. The observed diastereoselectivity was found to depend on the degree and pattern of chlorine substitution for hydrogen in the structure of the dehydroalanine complexes. The unsubstituted complex gave the ratio of diastereomers ( S )(2 S )/( S )(2 R ) of 66/34. On the other hand, introduction of chlorine atoms in the strategic positions on the chiral ligands allowed to achieve a practically attractive diastereoselectivity of (∼98.5/1.5). Diastereomerically pure major product was disassembled to prepare 9‐fluorenylmethyloxycarbonyl (Fmoc) derivative of ( S )‐4, 4‐difluoroglutamic acid. Abstract : The secret is in the structure ! An asymmetric Cu‐promoted Michael addition reaction between chiral Schiff base Ni(II)‐complexes and BrCF2 COOEt is developed providing an easy method for the synthesis of ( S )‐4, 4‐difluoroglutamic acid.